Circulating tumor DNA (ctDNA) in the era of personalized cancer therapy - Khatami, Fatemeh (J Diabetes Metab Disord, 2018)
The heterogeneity of tumor is considered as a major difficulty to victorious personalized cancer medicine. There is an extremeneed of consistent response evaluation for in vivo tumor heterogeneity anditscoupledconflict mechanisms. In this occasion researchers will be able to keep pace withpredictive, preventive, personalized, and Participatory (P4) medicine for cancer managements. In fact tumor heterogeneity is a central part of cancer evolution,soin order to progress in understanding of the dynamics within a tumor some diagnostic apparatus should be improved. Latest molecular techniques like Next generation Sequencing (NGS) and ultra-deep sequencing could disclose some clones within a liquid tumor biopsy which mainly responsible of treatment resistance. Circulating tumor DNA (ctDNA) as a main component of liquid biopsy is agifted biomarker for cancer mutation tracking as well as profiling. Personalized medicine facilitate learning regarding to genetic pools of tumor and their possible respond to treatment which could be much easier by using of ctDNA.With this information, cliniciansarelooking forward to find the best strategies for prevention, screening, and treatment in the way of precision medicine. Currently, numerous clinical efficacy of such informative improved treatment are in hand. Here we represent the review of plasma-derived ctDNA studies use in personalized cancer managements.